Kajian Preferensi Konsumen Rumah Tangga Terhadap Beras Organik di Wilayah Kota Bogor - Jimmy Rusma; Musa Hubeis; Budi Suharjo (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
Organic rice is an agricultural product which uses the system of organic diversification, is good for our health because it has no dangerous chemicals compared to other rice, has a specific aroma, does not easily go bad, and is tasty.  Because of its high price, only people of the middle to upper classes can afford to buy it.  It is expensive because it is chemical free, healthy, does not contain pesticide and farmers do not use inorganic fertilizers to grow it. The general objective of this study is to understand why people in Bogor buy organic rice.  Specifically, this study is (1) to identify the factors influencing the consumers’  decision in purchasing organic rice, (2) to evaluate the decision process to consume organic rice, and (3) to analyze the consumers’  behavior in order to organize the producer’s  marketing strategy of organic rice.  The study was conducted at Lembaga Pertanian Sehat (LPS) in Bogor.  Accidental sampling was conducted by interviewing 50 selected respondents who are consumers of organic rice.  Primary and secondary data were obtained through related literature and interviewing respondents through questionnaires.  The method of study used was the descriptive and quantitative analysis, using the Principal Component Analysis (PCA).  The data processing and analysis were conducted by using Microsoft Excel (tabulation, matrix correlation and Minitab V.10).  Consumers purchase organic rice through identification of needs, information search, alternative evaluation, buying process, and behavior after purchase.  If a respondent frequently purchases organic rice, he may not go through the process mentioned above.  Their need is health, the motivation to buy is the reasonable price, the stage of information search is usually through friends at work, neighbors, and self-initiative, in the alternative stage, the primary consideration is taste, in the buying stage it is the supply at home, and the nearness of location to buy it.  The average expenditure of organic rice is Rp 100,000-Rp 125,000 for four persons in a family. Six main variables influencing the purchase of organic rice are the quality, promotion, price, influence of friends and families.  The qualitative marketing strategy developed by producers covered products, price, promotion, and location. The marketing strategies were (1) product, (2) price, (3) promotion, and (4) location